INTERNATIONAL SEMINAR OF ENTREPRENEURSHIP - Andi Nurul Afdhal; Asmi Rahayu; Ismail Ismail; Misveria Misveria; Masyadi Masyadi; Azman Azman; Puji Rahmah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
In the digital era, entrepreneurship has undergone significant transformations, with digital business emerging as a key driver of innovation. The integration of advanced technologies such as Artificial Intelligence (AI), Internet of Things (IoT), blockchain, and big data analytics has revolutionized traditional business models, enabling entrepreneurs to create more efficient, scalable, and customer-centric ventures. Digital platforms facilitate access to a global market, reducing geographical barriers and enhancing communication channels. Furthermore, the rise of e-commerce, mobile applications, and cloud computing has provided new opportunities for business growth, while fostering a more dynamic and competitive business environment. This paper explores the role of innovation in entrepreneurship within the digital era, focusing on the shift towards digital business models, the impact of technological advancements on business strategy, and the emerging trends shaping the future of entrepreneurship. Ultimately, this study highlights the critical importance of adopting digital solutions for entrepreneurs aiming to thrive in the ever-evolving digital landscape.